Combination of methylprednisolone and rosiglitazone promotes recovery of neurological function after spinal cord injury - Xi-gong Li; Xiang-jin Lin; Jun-hua Du; San-zhong Xu; Xian-feng Lou; Zhong Chen (Neural Regeneration Research, 2016)
Methylprednisolone exhibits anti-inflammatory antioxidant properties, and rosiglitazone acts as an anti-inflammatory and antioxidant by activating peroxisome proliferator-activated receptor-γ in the spinal cord. Methylprednisolone and rosiglitazone have been clinically used during the early stages of secondary spinal cord injury. Because of the complexity and diversity of the inflammatory process after spinal cord injury, a single drug cannot completely inhibit inflammation. Therefore, we assumed that a combination of methylprednisolone and rosiglitazone might promote recovery of neurological function after secondary spinal cord injury. In this study, rats were intraperitoneally injected with methylprednisolone (30 mg/kg) and rosiglitazone (2 mg/kg) at 1 hour after injury, and methylprednisolone (15 mg/kg) at 24 and 48 hours after injury. Rosiglitazone was then administered once every 12 hours for 7 consecutive days. Our results demonstrated that a combined treatment with methylprednisolone and rosiglitazone had a more pronounced effect on attenuation of inflammation and cell apoptosis, as well as increased functional recovery, compared with either single treatment alone, indicating that a combination better promoted recovery of neurological function after injury.